The Art and Science of Planning at the Business Unit Level - Miesing, Paul; Wolfe, Joseph (Management Science, 1985)
This paper attempts to relate the conditions that require different planning approaches. A theoretical planning framework is presented that considers the confidence of causal linkages coupled with the extent of environmental change. Prior planning research is synthesized to speculate on the appropriate leadership and decision-making styles for single-businesses, nondiversified firms, or divisions of diversified firms. Examples of computational, consensual, contingency, and conceptual planning systems are also provided.